TOWARDS A CONCEPTUAL MODELLING OF TRANSFORMATIONAL LEADERSHIP - Zacharis, Konstantinos (IJRDO - Journal of Applied Management Science, 2016)
Modern educational systems are organized around patterns of leadership, which is considered a crucial element for their existence and cope with future change. In the current study, the new roles of leadership in contemporary education organizations are being asserted. Nowadays, the demands for a transformational-type of leadership inside a highly effective steering pattern are rising. At the same time, the need to incorporate ICT into the upper level functions of the hierarchy is obvious. What are the specific traits a leader has to possess in order to manage successfully an educational organization? What is principle-centered leadership and why is it appropriate for school principals? How can a novel leadership scenario foster innovation and performance and at the same time liberate schools from the tyranny of formal learning? What is the role of ICT artifacts along that process? The new generation of school leaders is called to answer these questions convincingly. To this aim, it has to redesign a cohesive vision based on student achievement and collaboration, to align all available resources (including curriculum, instruction and assessment). At the same time it should respect cooperate culture, sustain sub-systems, manage budgets, promote capacity learning and tune the whole structure towards excellence and high performance. This does sound, surely, as a challenging task.